Practical approach to revenue law - Mayson, Stephen W. (London, 1985)
This book is offered as no more than a commentary on the existing law relating to the major taxes of the United Kingdom, with the emphasis placed on the understanding of the important provisions of those taxes.
Keywords: Taxation law and legislation